Pengembangan Media Flip Chart Berbasis Model Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar Siswa Kelas 5 Gugus 2 Labuapi Tahun Ajaran 2021/2022 - Drestajumna, Putu; Istiningsih, Siti; Harjono, Harjono; Hakim, Mansur (Pendagogia: Jurnal Pendidikan Dasar, 2022)
Science subjects generally learn about how events occur around our nature or in other words it can also be called studying the earth itself. Learning outcomes are the results obtained by students in the process of teaching and learning activities at school. Not all learning outcomes obtained by students at the SDN are high, there are some students who have poor learning outcomes, especially in science subjects. Several factors in the learning process make learning outcomes cannot be achieved optimally such as monotonous methods, learning media that do not vary and many others that make student learning outcomes below average. The purpose of this research is to find out the steps for making flip chart media based on the NHT learning model in grade 5. To find out how the development of flip chart media can improve student learning outcomes in science subjects using the NHT method and its efficiency. The ADDIE development model is the development model used because the learning planning model is effective and efficient and the process is interactive, where the results of the evaluation of each phase can bring learning development to the previous phase. This model uses 5 stages, namely analysis, design, development, implementation, and evaluation. The research was conducted at SDN 2 Labuapi. The data collection tool uses a questionnaire. The results of the research on the effectiveness of the product are as expected because they get responses from both students and validators. Presentations by media experts, materials and the last student responses were: 78%, 86%, 91%. Looking at the order of responses, the effectiveness of media products was said to be very good in their use at school.